Spatial Analysis of the Urban Heat Island Distribution in Buraidah City Using Geographic Information Systems and the Google Earth Engine Platform (The International Journal for Scientific Research, 2026)
This study aims to explore and analyze the spatial pattern of the Urban Heat Island (UHI) phenomenon in Buraidah City by employing Geographic Information Systems (GIS) tools and utilizing the capabilities of the Google Earth Engine platform for processing and analyzing remote sensing data. The study relied on Landsat satellite imagery for the year 2025 to derive Land Surface Temperature (LST), along with the application of several spectral indices, including the Normalized Difference Vegetation Index (NDVI) and the Normalized Difference Moisture Index (NDMI), in order to analyze the relationship between thermal variations and land use/land cover patterns.The results revealed a noticeable spatial variation in the distribution of Land Surface Temperature values, ranging between 29°C and 57°C, with a clear dominance of high-temperature classes, reflecting the intensity of the Urban Heat Island effect within the urban fabric of the city. Furthermore, the results of spatial statistical analysis using Moran’s I Index indicated that the thermal distribution follows a clustered pattern with high statistical significance, where the index value reached 0.245, the z-score was 47.79, and the p-value was 0.000, confirming a strong spatial correlation among thermally similar areas. The study also confirmed an inverse relationship between vegetation density and temperature values, while higher thermal values were associated with barren and open areas characterized by low moisture levels.The importance of this study lies in presenting an integrated spatial analytical model that contributes to understanding the dynamics of Urban Heat Islands and provides a scientific basis to support decision-makers and planners in adopting sustainable urban planning policies. It also contributes to guiding efforts toward enhancing vegetation cover and improving land use patterns, thereby reducing negative environmental and climatic impacts within Buraidah City, in alignment with the objectives of Saudi Arabia’s Vision 2030, particularly in improving quality of life and enhancing energy efficiency.
Keywords: Urban Heat Island; Land Surface Temperature (LST); Google Earth Engine; Buraidah City